Analisis Kualitas Website Kompas.com Menggunakan Metode Webqual 4.0 - Cilma Fresha Perdana; Suprih Widodo (Journal of Information System Research (JOSH), 2025)
This study analyzes the quality of the Kompas.com website using the WebQual 4.0 method, which encompasses three main dimensions: usability, information quality, and service interaction quality. The research employed a quantitative approach, involving 40 respondents selected through purposive sampling. Data were collected via questionnaires using a four-point Likert scale and analyzed using statistical techniques. The findings indicate that all three website quality dimensions are categorized as "Good," with usability satisfaction at 79%, information quality at 81%, and service interaction quality at 76%. These results suggest that the Kompas.com website generally meets user expectations, although there is room for improvement, particularly in the aspect of service interaction.